Android-Based Traditional Games - Julianus, Ervan; Hidayat, Eka Wahyu; Sulastri, Heni (Universitas Trilogi, 2020)
The traditional Bentengan game is one of Indonesia's popular cultural heritages from the 1980s to the 1990s. Aside from being a cultural heritage, this game has benefits including for sports, training for concentration, or just for public entertainment. However, in the present where technology has become widespread, this game has begun to be almost forgotten and replaced by digital games. Therefore, we need a way to keep the game sustainable by utilizing the existence of technology, namely by changing the concept of traditional to modern. In this research the transformation process from traditional to modern games will be carried out using the ATUMICS method. The results of the transformation were developed into a 3D android game with additional online multiplayer features. Alpha test results using a black box showed that most of the application functions were running as expected, and the beta testing showed satisfactory results with an average overall rating of respondents saying 82% of digital games had the value of